Cost effectiveness of a systematic guidelines-based approach to the prevention and management of vascular disease in a primary care setting. (15th January 2016) - Kamboj, Laveena; Oh, Paul; Levine, Mitchell; Kammila, Srinu; Casey, William; Harterre, Don; Goeree, Ron
Abstract: Background: In Ontario, Canada, the Comprehensive Vascular Disease Prevention and Management Initiative (CVDPMI) was undertaken to improve the vascular health in communities. The CVDPMI significantly improved cardiovascular (CV) risk factor profiles from baseline to follow-up visits including the 10 year Framingham Risk Score (FRS). Although the CVDPMI improved CV risk, the economic value of this program had not been evaluated. Methods: We examined the cost effectiveness of the CVDPMI program compared to no CVDPMI program in adult patients identified at risk for an initial or subsequent vascular event in a primary care setting. A one year and a ten year cost effectiveness analyses were conducted. To determine the uncertainty around the cost per life year gained ratio, a non-parametric bootstrap analysis was conducted. Results: The overall population base case analysis at one year resulted in a cost per CV event avoided of $70, 423. FRS subgroup analyses showed the high risk cohort (FRS > 20%) had an incremental cost effectiveness ratio (ICER) that was dominant. In the moderate risk subgroup (FRS 10%–20%) the ICER was $47, 439 per CV event avoided and the low risk subgroup (FRS < 10%) showed a highly cost ineffective result of greater than $5million per CV event avoided. The ten year analysis resulted in a dominant ICER. Conclusions: At one year, the CVDPMI program is economically acceptable for patients at moderate to high risk for CV events. The CVDPMI results in increased life expectancy at an incremental cost saving to the healthcare system over a ten year period.